2011
DOI: 10.1186/2049-6958-6-4-220
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guided fine-needle aspiration biopsy of metastases in nonpalpable supraclavicular lymph nodes in lung cancer patients

Abstract: Background and objectivesTo assess frequency and significance of enlarged nonpalpable supraclavicular lymph nodes with routine ultrasound (US) evaluation and US-guided fineneedle aspiration biopsy (FNAB) for the diagnosis and staging of patients with lung cancer.Materials and methods106 consecutive patients with lung cancer and nonpalpable supraclavicular lymph nodes were evaluated with cervical US for the presence of pathological lymph nodes. FNAB was performed in patients with nodes with short-axis > 5 mm, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
0
9
1
Order By: Relevance
“…Davis et al reported the frequency of cervical lymph node involvement in patients with lung cancer, to vary from 1.5% to 32%, possibly because the term “cervical node” was used without site specification. High resolution ultrasound is extremely useful for imaging these patients . Prosch et al assessed the utility of ultrasound evaluation and ultrasound‐guided fine‐needle aspiration biopsy for the diagnosis and staging of patients with lung cancer.…”
Section: Specific Primary Tumor Sitesmentioning
confidence: 99%
“…Davis et al reported the frequency of cervical lymph node involvement in patients with lung cancer, to vary from 1.5% to 32%, possibly because the term “cervical node” was used without site specification. High resolution ultrasound is extremely useful for imaging these patients . Prosch et al assessed the utility of ultrasound evaluation and ultrasound‐guided fine‐needle aspiration biopsy for the diagnosis and staging of patients with lung cancer.…”
Section: Specific Primary Tumor Sitesmentioning
confidence: 99%
“…Presence of lower cervical lymphadenopathy indicates N3 disease corresponding to at least stage IIIB, and upper cervical lymphadenopathy represents M1b disease -stage IV lung cancer [2]. Neck ultrasound (NUS) routinely performed in patients with mediastinal lymphadenopathy has been shown to reveal metastases to neck lymph nodes in 40-50% of cases [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies in non-palpable supraclavicular nodes, detected and aspirated with US, confirmed these high rates of metastatic disease in lung cancer but the investigators did not perform PET imaging [55,56]. …”
Section: Us As a Sampling Guidementioning
confidence: 81%